Paradoxical-success imagery in the field - de la Pena, D.; Khoo, A.; Murray, N. P. (Journal of Imagery Research in Sport and Physical Activity, 2010)
In the current study, 27 male club-soccer players were trained with paradoxical-success imagery (de la Peña, 2009) in the field. Based on the tenets of Wegner's (1994) theory of ironic processes of mental control and previous research (e.g., de la Peña, 2009; Mellalieu et al., 2009), it was predicted that participants who imaged experiencing anxiety-related symptoms (combined with additional substantiated imagery components) prior to competing, would show a positive increase in self-confidence and interpretation of anxiety-related symptoms following training compared to pre-treatment. Hypotheses were supported in spite of an initial increase in cognitive anxiety intensity immediately following treatment. Additionally, results suggest that paradoxical-success imagery may be best suited for individuals with trait anxiety and the propensity to interpret anxiety-related symptoms as debilitative to performance. Factors contributing to the effective use of the imagery strategy as well as potential drawbacks are discussed.